Incidence of Coffee Leaf Rust in Vietnam, Possible Original Sources and Subsequent Pathways of Migration - Le, Cham Thi Mai; Okane, Izumi; Ono, Yoshitaka; Tsuda, Yoshiaki; Yamaoka, Yuichi (Frontiers in Plant Science, 2022)
This research focused on the incidence and population genetics of coffee leaf rust (CLR) fungus, Hemileia vastatrix, to estimate the possible original source(s) and subsequent migration pathways of wind-borne and human-aided spores in three main coffee production regions (Northwest, Central Highlands, and Southeast) in Vietnam. In southern Vietnam (Central Highlands and Southeast), Coffea canephora covers the majority area, while Catimor lines of C. arabica accounts for 95% of the coffee plantations in northwestern Vietnam. Field surveys conducted at eighty-five plantations, show coffee leaf samples infected by the rust fungus across forty-one plantations. Catimor varieties exhibited high levels of susceptibility with severe rust symptoms, while robusta varieties had varying degrees of susceptibility. We analyzed 863−869 base pairs of internal transcribed spacer (ITS) region from 83 samples (41 sequences from Vietnam, 2 from Thailand, and the remaining 40 from American countries); and fifty-two haplotypes consisting of 123 polymorphic sites were detected. Although the analysis of molecular variance (AMOVA) indicates significant genetic differentiation in the H. vastatrix populations in Vietnam, there was no clear genetic structure with respect to the three geographic areas surveyed. Based on the haplotype network, NeighborNet analysis, and geographical distribution patterns of the haplotypes, five haplotypes were identified as early established, from which most other haplotypes in Vietnam were derived. The early established haplotypes were found in the highest frequency in Northwest Vietnam. This finding corresponds to the earliest record of CLR in Vietnam. The phylogenetic network analysis also illustrated that H. vastatrix had expanded from the northwest to southern Vietnam. Pairwise genetic distance analysis and the geophylogenetic tree also suggests that CLR was first established in the Northwest. In addition, some scattered individuals on the principal coordinate analysis (PCoA) diagram and several separated haplotypes in the phylogenetic networks indicated that other branches of CLR in Vietnam were initiated in the Central Highlands. Hemileia vastatrix from these branches have been spreading in southern Vietnam.